ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERATAAN LABA PADA PERUSAHAAN INDUSTRI MANUFAKTUR DI INDONESIA PERIODE TAHUN 2017-2018 - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2020)
The results of statistical tests show that the t-value of the firm size variable in the t-test has a value of -2.020 which is smaller than the t-table which is 1.661, as well as the debit to equity ratio has a value of 0.292 or greater than the t-table, while profitability has a value of 1.453 which is more From the t-table, this proves that the debt to equity ratio and profitability that affect the income smoothing are only the size of the company which has no effect on income smoothing in manufacturing industrial companies in Indonesia if tested separately. However, the results of the f test also show that company size, debt to equity ratio, and profitability together (simultaneously) have no significant effect on income smoothing in manufacturing industrial companies in Indonesia. This result can be proven by the calculation that the significant value is 0.016 <0.05. The results of this study support the research conducted by Dhiar Ratnasari (2012) which also proves that the debt to equity ratio and profitability variables have an effect on income smoothing.